Analysis of patient with cervical discopathy treated surgically on the own material of neurosurgical department - Zygmunt Siedlecki; Kinga Kuriga; Weronika Bereźnicka; Maciej Śniegocki (Kazimierz Wielki University, 2020)
Cervical discopathy is an important medical problem widespread in society. Symptoms are often upper limbs radicular pain, local pain in the cervical spine, and vetrebrobasilar cerebrovascular insufficiency. In the case of ineffective conservative treatment and severe pressure on nerve structures, surgical treatment is indicated. Cervical discopathy is most common at the age of 30 - 60 with a predominance of women. The authors of this manuscript analyzed the medical data of patients operated on due to cervical discopathy on their own material. Cervical discopathy was found to be more common in women, which is consistent with world references. A relationship was found between cervical myelopathy and critical spinal canal stenosis and C4-C5 stenosis. Stenosis on C3-C4 has also been rare in female patients and more common in men. Obtained data on own material are generally consistent with reports from world literature and constitute its complement in reference to the region of the Kuyavian-Pomeranian Voivodeship.